Controlled mechanical assembly of complex 3D mesostructures and strain sensors by tensile buckling - Xiaogang Guo (Nature Portfolio, 2018)
Mesostructures: Complex 3D structures pop-up from 2D films 2D surfaces can be pulled into 3D structures just like a pop-up book. The transformation of 2D structures into complex 3D structures can be achieved by exploiting pre-stretched pre-patterned films- this is known as the compressive buckling method. Upon release, the pre-stretched film forms a 3D structure whose shape is dependant on how these films were pre-patterned. The requirement of pre-stretching may add complexity to the manufacturing process. Yihui Zhang and colleagues present an alternative approach to form 3D structures which bypasses the requirement of pre-stretching. The researchers- who are from Tsinghua University and Northwestern University- demonstrate the controlled mechanical assembly of 3D mesostructures by stretching pre-patterned 2D films- known as the tensile buckling method. Notably, their approach opens up 3D structures previously unobtainable via compressive buckling.